Inhibition of Renal Sodium–Glucose Cotransport With Empagliflozin Lowers Fasting Plasma Glucose and Improves β-Cell Function in Subjects With Impaired Fasting Glucose - Abdul-Ghani, Muhammad; Al Jobori, Hussein; Daniele, Giuseppe; Adams, John; Cersosimo, Eugenio; Triplitt, Curtis; DeFronzo, Ralph A. (Diabetes (New York, N.Y.), 2017)
The objective of this study was to examine the effect of renal sodium–glucose cotransporter inhibition with empagliflozin on the fasting plasma glucose (FPG) concentration and β-cell function in subjects with impaired fasting glucose (IFG). Eight subjects with normal fasting glucose (NFG) and eight subjects with IFG received empagliflozin (25 mg/day) for 2 weeks. FPG concentration and β-cell function was measured with a nine-step hyperglycemic clamp before and 48 h and 14 days after the start of empagliflozin. Empagliflozin caused 50 ± 4 and 45 ± 4 g glucosuria on day 2 in subjects with IFG and NFG, respectively, and the glucosuria was maintained for 2 weeks in both groups. The FPG concentration decreased only in subjects with IFG from 110 ± 2 to 103 ± 3 mg/dL (P < 0.01) after 14 days. The FPG concentration remained unchanged (95 ± 2 to 94 ± 2 mg/dL) in subjects with NFG. Empagliflozin enhanced β-cell function only in subjects with IFG. The incremental area under the plasma C-peptide concentration curve during the hyperglycemic clamp increased by 22 ± 4 and 23 ± 4% after 48 h and 14 days, respectively (P < 0.01); the plasma C-peptide response remained unchanged in subjects with NFG. Insulin sensitivity during the hyperglycemic clamp was not affected by empagliflozin in either IFG or NFG. Thus, β-cell function measured with the insulin secretion/insulin sensitivity (disposition) index increased significantly in IFG, but not in subjects with normal glucose tolerance. Inhibition of renal sodium–glucose cotransport with empagliflozin in subjects with IFG and NFG produces comparable glucosuria but lowers the plasma glucose concentration and improves β-cell function only in subjects with IFG.